2014
DOI: 10.1111/maec.12196
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on asexual reproduction of the scyphozoan Aurelia aurita s.l.: differences between exotic (Baltic and Red seas) and native (Mediterranean Sea) populations

Abstract: Massive occurrences of jellyfish can cause direct impacts on the economy, especially on tourism and commercial fisheries. Translocation of jellyfish species by humans has caused damaging blooms in new habitats. Aurelia aurita s.l. has been introduced in many locations around the world. To test the potential success of Au. aurita s.l. in various habitats, scyphistomae from different climatic locations (Mediterranean, Red and Baltic Seas) were cultured individually for 201 days at three temperatures (14, 21 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 49 publications
2
25
1
Order By: Relevance
“…In our study the Orkney population of A. aurita produced very few scyphistomae at 4°C and progeny were produced at temperatures beyond that with a general trend toward fewer progeny being produced at higher temperatures which was similar to results for scyphistomae of Aurelia labiata (Purcell, 2007). Furthermore several workers have suggested that Aurelia may be locally adapted (Connelly et al, 2001;Edwards, 1965;Lucas et al, 2012;Pascual et al, 2014;Schroth et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study the Orkney population of A. aurita produced very few scyphistomae at 4°C and progeny were produced at temperatures beyond that with a general trend toward fewer progeny being produced at higher temperatures which was similar to results for scyphistomae of Aurelia labiata (Purcell, 2007). Furthermore several workers have suggested that Aurelia may be locally adapted (Connelly et al, 2001;Edwards, 1965;Lucas et al, 2012;Pascual et al, 2014;Schroth et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…However, cosmopolitan species such as A. aurita, may also actually comprise a species complex as revealed by recent molecular studies (Dawson and Jacobs, 2001). Contrasting results may be the result of local adaptations suggesting that regionally focused studies will be required in order to predict population responses under climate change (Connelly et al, 2001;Edwards, 1965;Lee et al, 2013;Lucas et al, 2012;Pascual et al, 2014;Purcell, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, temperature and food availability appear to be the most important factors that synergistically affect scyphistoma reproduction and, subsequently, population growth in a positive or a negative way (see Schiariti et al 2014). In general, polyp-to-polyp reproduction rates increase with temperature and food supply (Lucas 2001;Lucas et al 2012;Purcell et al 2012;Pascual et al 2014). Within optimal ranges of these two key parameters, Aurelia scyphistomae propagate almost exclusively through NMB and ST, colonizing bare substrate very rapidly (Han and Uye 2010;Schiariti et al 2014;Melica et al, 2014;present study).…”
Section: Discussionmentioning
confidence: 92%
“…Aurelia scyphistoma strobilate repeatedly, are perennial and can produce new polyps and medusae for years (Arai 1997). During each strobilation event, polyps can produce as many as 40 ephyrae per polyp (Lucas et al 2012;Pascual et al 2014), and it is thus believed that asexual reproduction is a key driver of medusae blooms in coastal areas. Considering these features, in addition to the wide tolerance of Aurelia scyphistomae (and medusae) to environmental parameters (Lucas 2001;Lucas et al 2012), it is not surprising that the species/lineages of Aurelia are cosmopolitan and exhibit the most frequent bloom events.…”
Section: Discussionmentioning
confidence: 99%
“…Depth was an important predictor, as shown by Bosch et al (2018) and Snickars et al (2014) who suggested that bathymetry is of high relevance for modelling various taxa. Ice thickness was moderately important for phytobenthos and zooplankton, perhaps reflecting limits on distribution of the former due to ice abrasion, changes in light exposure and a preference of ice-free waters for the latter (Clark et al, 2013;Kube, Postel, Honnef, & Augustin, 2007;Pascual et al, 2015;Richardson, 1979). Iron was an important predictor for all modelled phytoplankton species, likely as it is known to be important to phytoplankton growth, abundance, dominance and species distributions (Hecky & Kilham, 1988;Moore et al, 2013) and plays a role in the development of harmful algal bloom species (Doucette & Harrison, 1990;Wells, Mayer, & Guillard, 1991).…”
Section: Discussionmentioning
confidence: 99%